The Impact of the Covid-19 Pandemic on Children and Adolescents Mental Health: A Literature Review - Dipa Ghosh (GLOBAL HEALTH SCIENCE GROUP, 2021)
The emergence of a new Coronavirus Disease 2019-2022 has turned the globe down and disrupted main determinants of health. The world constitutes by more than 2.2 billion children, which is approximately 28% of the world's population. Compare to adult, this pandemic has a long -term adverse consequences among children and adolescents. The objective of this literature review was to examine the impact of COVID-19 pandemic on children and adolescent’s mental health. PubMed and Google Scholar databases were searched from 07 April 2021 to 22 April 2021. A systematic literature search was performed in accordance with PRISMA and 07 literatures were selected. Among 16,169 samples, the mean percentage of male was higher 5 by 6.11% than female of 43.89%. Depression was mentioned in three studies and the percentages were 43.7% (n=8079), 22.6% (n=2330), and 22.8% (n=3613). Anxiety was mentioned in four studies and the percentages were 37.4% (n=8079), 18.9% (n=2330), and 23.87 ± 15.79 and 29.27 ± 19.79 (n=3613) and in one study according to CAQ and NRS, the level of anxiety was 19.4% and 21.8%. The combination of anxiety and depression was 31.3%. One study mentioned that pro social behaviour score was higher in females than males. In other two studies, various psychological symptoms are mentioned such as worry, fear, helplessness, boredom, difficulty in concentration, irritability, restlessness, nervousness, feeling of loneliness and uneasiness. These psychological symptoms have long-term effect on child’s health. Therefore, as a nurse, we should take care of the child and aware that the child and their parents regarding various psychological problems and its management.